Pertangungjawaban Pelaku Tindak Pidana Menjual Atau Menyediakan Rokok Kena Cukai Yang Tidak Terdaftar - Irsyadul Ikhsan; Zainab Ompu Jainah; Melisa Safitri (Universitas Sang Bumi Ruwa Jurai, 2023)
Cigarettes without excise duty or cigarettes with a hammer excise stamp on them can also be said to be illegal cigarettes with the characteristics of the original excise stamps including that the original excise stamps can be detected by naked eye, the hologram paper is usually green with the Indonesian symbol but the color can change every year, and Original excise tape paper has worm-like fibers and watermarks. Cigarettes that are mandatory for distribution in Indonesia can be achieved with business legality, production legality, and promotion legality as the bureaucracy of cigarette distribution in Indonesia. And as explained above, that smoking is a product of processed tobacco, in accordance with Law Number 39 of 2007 concerning Excise, cigarette packages must be affixed with and attached with excise tape as proof of excise payment so that cigarettes can be said to be legal to offer, hand over, provided for sale. Law Number 39 of 2007 concerning Excise also regulates that cigarettes that circulate without excise bands and do not comply with the applicable laws are said to be illegal cigarettes, anyone who distributes them can be said to be against the law and can be subject to imprisonment and fines.